ANALISIS DAMPAK POLUSI CAHAYA LAMPU ARTIFISIAL TERHADAP KECERLANGAN LANGIT MALAM MENGGUNAKAN SKY QUALITY METER (Studi Kasus Barus-Sumatera Utara): Studi Kasus Barus-Sumatera Utara - Firdaus, Muhammad Dimas; Butar-Butar, Arwin Juli Rakhmadi; Putraga, Hariyadi; Hidayat, Muhammad (ELFALAKY: Jurnal Ilmu Falak, 2022)
The brightness of the night sky is a necessity in astronomical observations. Sky with minimal light pollution can be optimized for observation and research. Light pollution is an obstacle in astronomical observations, one of the light pollution that affects the night sky a lot is artificial lights that are not properly conditioned. In this study, it is explained how the impact of artificial lights on good sky brightness using the Sky Quality Meter (SQM). By observing several nights, it was found that locations with a lot of light exposure can make the sky brighter ~3.3 times compared to locations with minimal light.